Volatile oil composition of four popular varieties of large cardamom (Amomum subulatum Roxb.) - Vijayan, A K; Leela, N K; Dhanalakshmi, M; Akshitha, H J; Rahul, R; Utpala, P; Babu, K N (Journal of Spices and Aromatic Crops, 2017)
In the present study volatile oil profile of the four popular varities of large cardamom (Amomum subulatum Roxb.) namely Sawney, Varlangey, Ramla and Ramsey were studied in detail. The capsules contained 58.1- 68.1% seeds and 1.2-2.8% essential oil. By GC-MS analysis 23 constituents of the oil were identified with 1, 8- cineole as the chief component. Major constituents of the oil were ?-pinene (1.7-6.5%), ? - pinene (4.0-11.1%), 1, 8- cineole (63.2-73.4%) and ?- terpineol (5.6-7.6%). The oil contained high level of 1, 8- cineole when compared to small cardamom (Elettaria cardamomMaton). ? -Terpinyl acetate, the chief component of small cardamom oil was not detected in large cardamom.